Cumulative COVID‐19 incidence, mortality and prognosis in cancer survivors: A population‐based study in Reggio Emilia, Northern Italy. Issue 4 (27th April 2021) - Mangone, Lucia; Gioia, Francesco; Mancuso, Pamela; Bisceglia, Isabella; Ottone, Marta; Vicentini, Massimo; Pinto, Carmine; Giorgi Rossi, Paolo
Abstract: The aim of this population‐based study was to evaluate the impact of being a cancer survivor (CS) on COVID‐19 risk and prognosis during the first wave of the pandemic (27 February 2020 to 13 May 2020) in Reggio Emilia Province. Prevalent cancer cases diagnosed between 1996 and 2019 were linked with the provincial COVID‐19 surveillance system. We compared CS' cumulative incidence of being tested, testing positive for severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), being hospitalized and dying of COVID‐19 with that of the general population; we compared COVID‐19 prognosis in CS and in patients without cancer. During the study period, 15 391 people (1527 CS) underwent real‐time polymerase chain reaction for SARS‐CoV‐2, of whom 4541 (447 CS) tested positive; 541 (113 CS) died of COVID‐19. CS had higher age‐ and sex‐adjusted incidence rate ratios (IRR) of testing (1.28 [95% confidence interval, CI = 1.21‐1.35]), of positive test (IRR 1.06 [95% CI = 0.96‐1.18]) and of hospitalization and death (IRR 1.27 [95% CI = 1.09‐1.48] and 1.39 [95%CI = 1.12‐1.71], respectively). CS had worse prognosis when diagnosed with COVID‐19, particularly those below age 70 (adjusted odds ratio [OR] of death 5.03; [95% CI = 2.59‐9.75]), while the OR decreased after age 70. The OR of death was higher for CS with a recent diagnosis, that is, <2 years (OR = 2.92; 95% CI = 1.64‐5.21), or metastases (OR = 2.09; 95% CI = 0.88‐4.93). CS showed the same probability of being infected, despite a slightly higher probability of being tested than the general population. Nevertheless, CS were at higher risk of death once infected. Abstract : What's new Immunosuppressed status caused by cancer or cancer treatment has been suggested to increase the risk of SARS‐CoV‐2 infection and worse outcomes in cancer patients compared to the general population. This study in an Italian province with a high tumour incidence rate that saw a high cumulative COVID‐19 incidence found that, during the first wave, the cumulative incidence of COVID‐19 in cancer survivors was similar to that in the general population, despite their slightly higher probability of being tested. Cancer survivors had a greater risk of hospitalisation and death once infected, especially if aged <70 years or recently diagnosed with cancer.